Effects of Detraining on Elderly Women's Health Post-Exercise - Hadi, Santika Rentika; Abdul Rahim, Mohamad Rahizam; Irmawati, Anis; Hayati, Hayati; Rohman, Ujang (Jurnal Pendidikan Jasmani Indonesia, 2023)
Physical inactivity is a significant risk factor for numerous chronic diseases, including cardiovascular conditions and type 2 diabetes, particularly in aging populations. Resistance training has been shown to reduce systemic inflammation and preserve muscle mass, which can mitigate the impacts of aging. However, the regressive effects of detraining on older adults' health outcomes remain underexplored. This study aimed to investigate the effect of a three-month detraining period following a nine-month multicomponent training program on cardiorespiratory fitness, lipid profiles, glycemic control, and hemodynamic status in older women. Fifty-six Asian women aged 58–70 were divided into an experimental group (EG) and a control group (CG). The EG participated in a nine-month exercise program, which included cardiorespiratory, strength, balance, and flexibility training. After this, both groups underwent three months of detraining. The results showed that the EG experienced significant declines in body weight, BMI, and cardiorespiratory fitness following detraining, with adverse effects on lipid and glycemic profiles. The findings suggest that even a short period of detraining can lead to the loss of metabolic and functional benefits from long-term exercise, emphasizing the importance of maintaining regular physical activity to sustain health in aging populations.